1057. Treatment Efficacy of Ceftriaxone vs. Cefazolin for Methicillin-Susceptible Staphylococcus aureus Infections. (26th November 2018) - Bhavan, Kavita; Ganguly, Anisha; King, Helen; Schmalstieg, Aurelia; Mang, Norman; Collins, Ryan
Abstract: Background: Methicillin-susceptible Staphylococcus aureus (MSSA) infections are traditionally treated with intravenous (IV) nafcillin, oxacillin, or cefazolin, all antibiotics that require multiple doses per day. Despite theoretical limitations of using ceftriaxone in MSSA infections, some clinical studies suggest noninferiority of ceftriaxone compared with standard of care. At Parkland Memorial Hospital, many patients diagnosed with MSSA infections receive self-administered Outpatient Parenteral Antimicrobial Therapy (S-OPAT). Daily-dosed ceftriaxone is often used for convenience and feasibility of medication adherence. Methods: We conducted a retrospective cohort study among S-OPAT patients receiving cefazolin and ceftriaxone for treatment of MSSA infections. We compared infection type and planned duration of therapy as baseline differences between the treatment cohorts. Our clinical outcomes of interest were 30-day readmission rates and treatment failure as defined by repeat positive blood culture within 6 months. Results: We identified 184 patients treated with cefazolin and 74 patients treated with ceftriaxone. Characteristics of treatment plan are shown in Table 1. There were no statistically significant differences in infection type or mean duration of therapy between the two treatment cohorts. Outcomes are shown in Table 2. There were no statistically significant differences in readmission rates and rate of treatment failure. Conclusion: Our retrospective review suggests patients treated with ceftriaxone for MSSA bacteremia had similar clinical outcomes as those treated with cefazolin. While this study is limited in its retrospective nature, the findings suggest that ceftriaxone may be a safe and more convenient antibiotic option in certain MSSA infections. Disclosures: All authors: No reported disclosures.